Pendistribusian Zakat Bagi Korban Bencana Alam di Sumatera dalam Kerangka Regulasi BAZNAS - Ansori, Moh. Asep Zakariya; Husenudin, Abdul; Akmalia, Lili; Saputra, M Galih; Syalumita, Annisa (Ikatan Da'i Indonesia, 2026)
The distribution of zakat for disaster victims constitutes a strategic form of socio-religious intervention in addressing economic vulnerability and humanitarian crises. Sumatra, as a region with a high level of disaster risk, requires a zakat distribution mechanism that is not only responsive and timely, but also firmly grounded in regulatory policy and principles of sound zakat governance. This article aims to analyze the distribution of zakat for natural disaster victims in Sumatra within the regulatory framework of the National Zakat Board (BAZNAS), particularly referring to BAZNAS Regulation Number 3 of 2018 concerning Zakat Distribution and Utilization. This study employs a juridical-normative approach with a descriptive-analytical method through library research, examining the conformity between legal norms, policy implementation, and the effectiveness principles of zakat distribution. The findings indicate that, from a normative perspective, zakat distribution for disaster victims has obtained strong legal legitimacy, both through the classification of eligible beneficiaries (asnaf) and the designation of humanitarian assistance as a formal sector of zakat distribution. Nevertheless, at the level of implementation, several challenges remain, including limitations in beneficiary verification, inconsistencies in monitoring mechanisms, and variations in distribution effectiveness. This article underscores the importance of strengthening regulation-based zakat governance and effectiveness to ensure that zakat distribution for disaster victims is not only legally valid but also optimal in achieving broader social welfare objectives.